1987
DOI: 10.3168/jds.s0022-0302(87)80265-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stage of Cycle, Corpus Luteum Location, Follicle Size, and Number of Large Follicles on Estradiol-17β Concentrations in Bovine Follicles

Abstract: Concentrations of estradiol-17 beta in follicular fluid were correlated to follicular size, stage of estrous cycle, location of corpus luteum, and presence of large follicles. Paired ovaries were obtained from 481 nonpregnant cows at slaughter and follicles were classified as ipsilateral or contralateral to the corpus luteum. Follicular fluid estradiol-17 beta concentrations from 2494 small, 1485 medium, and 396 large follicles were quantified by radioimmunoassay. Stage of estrous cycle was estimated by visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, both the buffaloes had follicles in their ovaries. The same relationship between the size and number was reported in cows [19]. Ginther et al [20] reported a decrease in the dominant follicle diameter after day 90 of cow pregnancy.…”
Section: Resultssupporting
confidence: 65%
“…However, both the buffaloes had follicles in their ovaries. The same relationship between the size and number was reported in cows [19]. Ginther et al [20] reported a decrease in the dominant follicle diameter after day 90 of cow pregnancy.…”
Section: Resultssupporting
confidence: 65%
“…Thus, it was expected that most of the medium (subordinate) follicles would suffer FSH insufficiency and undergo atresia at this stage of follicle selection 37 . In both cows 38 and sows 39 , the concentration of E2 increased significantly with increasing follicular sizes. Studies in the human suggested that GDF9 levels in the follicular fluid were highly correlated with oocyte nuclear maturation and embryo quality 40 .…”
Section: Discussionmentioning
confidence: 92%
“…The presence of a corpus luteum had no effect on the follicle hormone concentration within sets of ovaries. Thus, it can be accepted that corpora lutea have no direct influence on steroid concentration within follicles (Brantmeier and others 1987).…”
Section: Granulosa Theca Degenerate Active Round Flattenedmentioning
confidence: 99%